Illustrated Pollen Terminology - Halbritter, Heidemarie (Springer International Publishing, 2018)
This open access book offers a fully illustrated compendium of glossary terms and basic principles in the field of palynology, making it an indispensable tool for all palynologists. It is a revised and extended edition of "Pollen Terminology. An illustrated handbook," published in 2009. This second edition, titled "Illustrated Pollen Terminology" shares additional insights into new and stunning aspects of palynology. In this context, the general chapters have been critically revised, expanded and restructured. The chapter "Misinterpretations in Palynology" has been extended with new research data and additional ambiguous terms, e.g., polyads vs. massulae; the chapter "Methods in Palynology" has been extensively enhanced with illustrated protocols showing the majority of the methods and techniques used when studying recent and fossil pollen with LM, SEM and TEM. Moreover, additional information about the description and publication of pollen data is provided in the chapter "How to Describe and Illustrate Pollen Grains." Various other parts of the general chapters have now been updated and/or extended with more comprehensive textual passages and new illustrations. The chapter "Illustrated Pollen Terms" now features new and more appropriate examples of each term, including additional LM micrographs. Where necessary, the entries for selected pollen terms have been refined by rewording or adding definitions, illustrations, and new micrographs. Lastly, new terms are included, such as "suprasculpture" and the prefix "nano-" for ornamentation features. The chapter "Illustrated Pollen Terms" is the main part of this book and comprises more than 300 widely used terms illustrated with over 1,000 high-quality images. It provides a detailed survey of the manifold ornamentation and structures of pollen, and offers essential insights into their stunning beauty.